(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The study aims to determine the significance of the educational sector development plan as perceived by the planning department of the Ministry of Education. Furthermore,it seeks to explore differences in perspectives on the necessity of the educational sector development plan among individuals who adapt to change, considering factors such as( years of experience and academic qualifications). A descriptive analytical approach was employed for this study. The primary study tool utilized was a questionnaire, structured around four key objectives: (administrative/organizational requirements, essential requisites, material prerequisites, and technical specifications). The study involved a sample of (49) planning professionals, both male and female, from the Ministry of Education. These participants were carefully selected and identified. Subsequently, the questionnaire was administered to measure their perspectives on the necessary components for an effective educational sector development plan, following thorough validation procedures. The research findings indicated a moderate level of fulfillment across all aspects of the educational sector development plan requirements, with the exception of technical requirements, which were observed to have a low level of availability. Moreover, no statistically significant differences were found in the average scores of the study sample members on the questionnaire based on the variable of experience. Regarding the variable of academic qualifications, there were no statistically significant differences in the average scores of the research sample members on the questionnaire in the(financial and technical requirement subcategories). However, differences were observed in the( administrative-organizational and human requirement subcategories).